2021
DOI: 10.1186/s40949-021-00060-4
|View full text |Cite
|
Sign up to set email alerts
|

The microbiome’s relationship with congenital heart disease: more than a gut feeling

Abstract: Patients with congenital heart disease (CHD) are at risk for developing intestinal dysbiosis and intestinal epithelial barrier dysfunction due to abnormal gut perfusion or hypoxemia in the context of low cardiac output or cyanosis. Intestinal dysbiosis may contribute to systemic inflammation thereby worsening clinical outcomes in this patient population. Despite significant advances in the management and survival of patients with CHD, morbidity remains significant and questions have arisen as to the role of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 124 publications
0
9
0
Order By: Relevance
“…Additional factors thought to play a role in the pathogenesis of cardiac NEC are similar to those of classical NEC. Pathogenic bacteria likely to translocate the ischemically compromised intestinal epithelium in cardiac NEC originate from an altered microbiome, similar to that of classical NEC [ 51 ], but in the case of cardiac NEC, have likely proliferated due to intestinal hypoperfusion, venous congestion and bowel wall edema, and associated inflammation [ 52 ]. Infants with cardiac NEC harbor additional Firmicutes, but reduced Actinobacteria, Bacteroidetes, and Enterobacteriaceae, as well as reduced total bacterial counts, compared with healthy controls [ 53 ].…”
Section: Pathogenesis Of Intestinal Injury In Congenital Heart Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Additional factors thought to play a role in the pathogenesis of cardiac NEC are similar to those of classical NEC. Pathogenic bacteria likely to translocate the ischemically compromised intestinal epithelium in cardiac NEC originate from an altered microbiome, similar to that of classical NEC [ 51 ], but in the case of cardiac NEC, have likely proliferated due to intestinal hypoperfusion, venous congestion and bowel wall edema, and associated inflammation [ 52 ]. Infants with cardiac NEC harbor additional Firmicutes, but reduced Actinobacteria, Bacteroidetes, and Enterobacteriaceae, as well as reduced total bacterial counts, compared with healthy controls [ 53 ].…”
Section: Pathogenesis Of Intestinal Injury In Congenital Heart Diseasementioning
confidence: 99%
“…Unfortunately, small clinical trials administering probiotics in infants undergoing CHD surgery have yet to demonstrate a reversal of this dysbiosis, nor significant benefits to the infant [ 53 , 54 ]. This enduring hypoperfusion-induced dysbiosis further weakens the intestinal barrier, allowing inflammatory molecules such as trimethylamine N-oxide (TMAO) to additionally activate the endothelium [ 52 ]. Low blood flow, in combination with the induced overgrowth of proinflammatory, facultative anaerobes spurred by this low oxygen environment, induce upregulation of hypoxia inducible factor-1 alpha (HIF-1α) and NF-κB (nuclear transcription factor-κB), the latter influenced by either a reduction in butyrate-producing organisms [ 52 ] or crosstalk with HIF-1α [ 55 ].…”
Section: Pathogenesis Of Intestinal Injury In Congenital Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge about the gut microbiome of infants with CHD is only beginning to emerge, [64][65][66][67][68][69] and there has been no investigation into HM composition in the context of CHD. A 2022 study by Huang et al.…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…64 The authors propose Bifidobacterium and oligosaccharide supplementation for infants with critical CHD, but stop short of recommending improved lactation support for these infants and their families as a mechanism to promote intestinal homeostasis. Of the remaining abstracts, 69 studies, 65,67,68 or reviews 66 identified on the topic of the gut microbiome in patients with CHD, only one briefly mentions HM/BF 68 and none discuss HM/BF as a therapeutic intervention for gut dysbiosis.…”
Section: Potential Mechanismsmentioning
confidence: 99%